A Study on Pregnancy, Perceived Stress and Depression - Deo, Binod Kumar; Sapkota, Nidesh; Kumar, Rajesh; Shakya, Dhana Ratna; Thakur, Achala; Lama, Sami (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Pregnancy can be a difficult period during which psychosocial and hormonal changes may lead to increased incidence of mental health problems such as stress, depression, anxiety and obsessive compulsive disorders. Objective: a. To describe the clinical and socio-demographic profile, b. to explore the level of stress and c. to assess the depression among the pregnant women. Methods: It was a hospital based study using convenient and purposive sampling where only pregnant women were selected for study in 1 year. Instruments used were: the Perceived Stress Scale(Sheldon Cohen), Social Readjustment Scale (Holmes and Rahe) and General Health Questionnaire-12 (David Goldberg). Results: About 2/3rd of pregnant women were from age range 15-25 years, 49% were housewives and all literate. Patients were mainly from Sunsari and Morang districts. About 28% patients were mild to moderately stressed. About 50% patients were on 50% zone of possibility of sickness on the Social Readjustment Rating Scale. About 50% patients were mild to moderately depressed. Conclusion: One third of pregnant women were mild to moderately stressed. Nearly half number of the clients were mild to moderately depressed and were in moderate to severe range at > 50% risk for developing sickness.